Knowledge and prevalence of trauma and evaluation of the impact of educational and preventive actions on a population of athletes (Research, Society and Development, 2021)
This university extension project aimed to verify the knowledge of athletes about dental trauma, the prevalence and type of trauma that occurred in sports, previous use of mouthguards and to evaluate the impact of educational/preventive actions implemented in this population. The study was divided into 1) Application of Questionnaire 1 (n=94); 2) Clinical examination and manufacture of mouthguards; 3) Lecture on trauma; 4) Application of questionnaire 2 (n=40). The data were submitted to descriptive analysis and Fisher's exact test, with a significance of 5%. Athletes showed little knowledge about dental trauma. The prevalence of trauma and previous use of the protector were higher in athletes in the fighting sports category (p